Stratton, Biggleswade : 1,300 years of village life in eastern Bedfordshire from the 5th century AD - Shotliff, Drew, (Archaeopress Archaeology, 2022)
This is the results of 12 hectares of archaeological excavation undertaken between 1990 and 2001. As well as uncovering roughly half of the medieval village, the investigations revealed that Stratton's origins stretched back to the early Anglo-Saxon period, with the settlement remaining in continuous use through to c. 1700. In contrast to many of the other major excavations of Anglo-Saxon settlements, the evidence from Stratton provides insights into the lives of a low-status rural community, whose development can be traced over the course of more than a millennium. This book presents a chronological account of Stratton's development; evidence for its economy, trading relations, industrial activities and agricultural landscape; and a discussion of how people lived and died there before the village was finally extinguished by the creation of the classic estate landscape of Stratton Park.